2019
DOI: 10.1177/1098612x19838286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative complication rates in cats undergoing perineal urethrostomy performed in dorsal recumbency

Abstract: Case series summary Medical records were reviewed for cats that underwent a perineal urethrostomy performed in dorsal recumbency for the treatment of urethral obstruction. Information, including signalment, reason for presentation, number of previous obstructions, surgery time, and perioperative and postoperative complications, were collected through a review of medical records and owner follow-up. The objective was to evaluate short- and long-term complications in cats that underwent perineal urethrostomy per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The most common late complication is bacterial urinary tract infection, which affects 17-57% of cats undergoing perineal urethrostomy. 55 Ruda and Heiene found that clients consider their pet to have a good quality of life after this procedure. 53 A modified perineal urethrostomy technique has been published by Yeh and Chin that uses the preputial mucosa for anastomosis with the pelvic urethra.…”
Section: Urinary Tract Trauma Conditionsmentioning
confidence: 99%
“…The most common late complication is bacterial urinary tract infection, which affects 17-57% of cats undergoing perineal urethrostomy. 55 Ruda and Heiene found that clients consider their pet to have a good quality of life after this procedure. 53 A modified perineal urethrostomy technique has been published by Yeh and Chin that uses the preputial mucosa for anastomosis with the pelvic urethra.…”
Section: Urinary Tract Trauma Conditionsmentioning
confidence: 99%
“…Urethral strictures and urethrostomy overgrowth, according to different authors, range from 12% [12] to 35% [13]. Recurrent urinary tract infection is observed in more than 30% of cats undergoing perineal urethrostomy and in more than 60% of cats undergoing prepubic urethrostomy [14,15]. Complications such as postoperative urinary tract infections are also observed after cystotomy [16].…”
Section: Fig 1 Confidence Intervals For 3 Diseases In the Intervention And Controlgroupsmentioning
confidence: 99%